THE PRINCIPLES OF THOUGHT AND GENERAL VISION OF EDUCATION ACCORDING TO IBN TAYMIYAH - Fadkhulil Imad Haikal Huda; Farid Setiawan (Proceeding International Seminar of Islamic Studies, 2022)
This study discusses the theory of principles of thought and the general vision of education brought by Ibn Taymiyah. The whole thought of Ibn Taymiyah in education is built based on the primary reference of the Muslim ummah, namely the Qur'an and the Sunnah. Such thinking became one of the forms of response in solving problems that occurred in his time through the approach of education. To obtain this research, the authors used the approach of Library Research. Ibn Taymiyah's principles of educational thinking emphasize the aspects of aqeedah and Tawheed which are the basis in seeking knowledge. The results of this discourse are that the principle of Ibn Taymiyah's thought emphasizes the aspects of aqeedah and Tawheed. There are used as a shield and direction in specific guidance on educational activities. Making al-Fitrah or the heart as the truth in guiding knowledge, tawheed education as a form of glorifying Allah Swt, and the human tabi'at who always worship their Lord. This is implemented into three aspects of the general vision of education, including (1) The individual vision, (2) the social vision, and (3) the vision of Islamic da'wah.Keywords: Ibn Taymiyyah, The Principles of Thought, The General Vision of Education